Hasidic Myth-Activism: Martin Buber's Theopolitical Revision of Volkish Nationalism - Hadad, Yemima (Religions, 2019)
Since the 1970s, Buber has often been suspected of being a Volkish thinker. This essay reconsiders the affinity of Buber's late writings with Volkish ideology. It examines the allegations against Buber's Volkish thought in light of his later biblical and Hasidic writings. By illuminating the ideological affinity between these two modes of thought, the essay explains how Buber aims to depart from the dangers of myth without rejecting myth as such. I argue that Buber's relationship to myth can help us to explain his critique of nationalism. My basic argument is that in his struggle with hyper-nationalism, Buber follows the Baal Shem Tov and his struggle against Sabbateanism. Like the Besht, Buber does not reject myth, but seeks instead to repair it from within. Whereas hyper-nationalism uses myth to advance its political goals, Buber seeks to reposition ethics within a mythic framework. I view Buber's exegesis and commentaries on biblical and Hasidic myths as myth-activism.